O uso das TDICs na área de CALL: um estudo de caso sobre o ensino e a aprendizagem de língua inglesa em uma escola online - Franchi-Mello, Ana (Universidade Federal de São Carlos, 2025)
This study aims to investigate the process of teaching and learning English in an online school setting (Krashen 1982, Ellis 1994, Swain 1985, Vygotsky 1934). It seeks to understand how students perceive their learning, the facilitators and obstacles they encounter while learning English, taking into account Digital Information and Communication Technologies (DICTs), based on the field of CALL in a specific Online School (Garret 2009, Leffa 2006, Finardi & Porcino 2014, Martins & Moreira 2012, Ribeiro 2016, 2020, 2021, Coscarelli 2022, Carvalho, Sataka & Rozenfeld 2023, Rabello 2021). A qualitative-interpretative approach was chosen, in the form of a case study (Yin, 2005). Data collection involved non-participant observation with field notes, questionnaires with teachers and students, and documentary sources (Lakatos & Marconi, 2003). Once collected, the data were triangulated, discussed, and analyzed. The study presents a description of the process of learning the English language through the DICTs used in CALL-based classes, from the perspective of students regarding their language development and the teacher's perception of their teaching approach. Learning English in an online language school can offer a contextualized and convenient approach for students, allowing them the opportunity to develop language skills at their own pace. However, it is essential that teachers adapt to the demands of the virtual environment by adopting effective teaching strategies and fostering meaningful interaction (Barros Nunes, 2009). Overcoming the inherent challenges of online teaching is crucial to ensuring a rich and successful learning experience for students. Thus, this study aims to contribute to the ongoing discussions about the role of online English teaching through DICTs within the field of CALL.
The use of ICTs in the area of ​​CALL: a case study on english language teaching and learning in an online school
Keywords: Ensino e aprendizagem de língua inglesa; Escola de inglês online; CALL e TDICs; English language teaching and learning; Online english school; CALL and DICTs; LINGUISTICA, LETRAS E ARTES::LINGUISTICA::LINGUISTICA APLICADA